Fungal Community of Culturable Fungal Endophytes Associated with Cinchona calisaya Collected from Gambung, West Java, Indonesia - Hidayat, Iman; Radiastuti, Nani; Rahayu, Gayuh; Okane, Izumi (Makara Journal of Science, 2019)
Previous studies regarding endophytic fungi associated with Cinchona were focused on the analysis of quinine and related fungal metabolites. In the current study, the community structure of culturable endophytic fungi associated with C. calisaya (i.e., leaf, petiole, twig, root, flower, and fruit) were analyzed and elucidated. Representative isolates from various morphotypes were identified based on a sequence generated from the Internal Transcribed Spacer (ITS) rDNA region. A total of 638 fungal strains were isolated from 700 plant segments. All isolates belong to the phylum Ascomycota and are dominated by a member of Sordariomycetes. The fungal endophyte community within C. cali-saya consists of 23 known species, 10 species complexes, and 6 unidentified species. Based on the Shannon-Wiener diversity index, the leaves and fruits host the most diverse endophytic fungi, followed by twigs, petioles, and bark. Members of the genus Diaporthe are commonly found in all C. calisaya organs. Neofussicoccum sp. was only one found within twigs; the Colletotrichum gloeosporioides complex and Guignardia mangiferae were only found within leaves; the C. brasiliense complex was detected in flowers; and Fusarium oxysporum is specific to roots.